SARS-CoV-2 Spike protein alters microglial purinergic signaling - Alves, Vinícius Santos; Santos, Stephanie Alexia Cristina Silva; Leite-Aguiar, Raíssa; Paiva-Pereira, Elaine; Reis, Renata Rodrigues dos; Calazans, Mariana L.; Fernandes, Gabriel Gripp; Antônio, Leticia Silva; de Lima, Emanuelle V.; Kurtenbach, Eleonora; Silva, Jerson Lima; Fontes-Dantas, Fabricia Lima; et al. (Frontiers in Immunology, 2023)
Despite long-term sequelae of COVID-19 are emerging as a substantial public health concern, the mechanism underlying these processes still unclear. Evidence demonstrates that SARS-CoV-2 Spike protein can reach different brain regions, irrespective of viral brain replication resulting in activation of pattern recognition receptors (PRRs) and neuroinflammation. Considering that microglia dysfunction, which is regulated by a whole array of purinergic receptors, may be a central event in COVID-19 neuropathology, we investigated the impact of SARS-CoV-2 Spike protein on microglial purinergic signaling. Here, we demonstrate that cultured microglial cells (BV2 line) exposed to Spike protein induce ATP secretion and upregulation of P2Y6, P2Y12, NTPDase2, and NTPDase3 transcripts. Also, immunocytochemistry analysis shows that spike protein increases the expression of P2X7, P2Y1, P2Y6, and P2Y12 in BV2 cells. Additional, hippocampal tissue of Spike infused animals (6,5ug/site, i.c.v.) presents increased mRNA levels of P2X7, P2Y1, P2Y6, P2Y12, NTPDase1, and NTPDase2. Immunohistochemistry experiments confirmed high expression of the P2X7 receptor in microglial cells in CA3/DG hippocampal regions after spike infusion. These findings suggest that SARS-CoV-2 Spike protein modulates microglial purinergic signaling and opens new avenues for investigating the potential of purinergic receptors to mitigate COVID-19 consequences.